شفـرات الأداء الجسدي للممثل فـي المسرح العراقي - Haider Salih Dashr ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The Department of Arts, including the theater, is expanding its interdisciplinary interactions Criticism and philosophy This is a milestone in the twentieth century, which is The impact on theatrical activity most of the most Its trends, trends and experiences. The dominance of criticism and philosophy and its effects on the stage is a necessity Required to track the proportion of the process of composition and preparation of the play, There is no doubt that the representative is one of the most important technical elements that He cannot be dispensed with as a living being His daily movements are many performance codes trying to benefit As representative with the rest of the elements and ideas of the presentation as influential signs In the formulation of the speech theater presentation. Which prompted the researcher to investigate the most important codes performance of the body of the actor and how to understand and benefit from them. Formation and preparation of the presentation form artistically, philosophically and aesthetically. This opened the door to the detailed research tagged, (codes performance of the actor in the Iraqi theater) the following divisions: First: Chapter One: Methodological Framework Second: Chapter Two: Theoretical framework The first subject: body and theater The second subject: the body and the significance of the play Third: The research procedure The researcher chose the research samples that fit the research objectives that he seeks to achieve. The play "Othello" is written by Ali Talib. The fourth chapter guarantees the search results, sources and references